Edukasi Bahaya Napza (Narkotika, Psikotropika, dan Zat Adiktif) bagi Remaja SMA Muhammadiyah Sumbawa - Asri Reni Handayani; Nur Arifatus Sholihah (Lembaga Pengembangan Kinerja Dosen, 2023)
Adolescence is a transitional period between childhood and adulthood, which begins at the time of sexual maturity between the ages of 11 or 12 years to 20 years. The stages of adolescent development have tasks that must be completed. Drug abuse is becoming a problem that is increasingly concerning and a huge concern for all parties, including the academic community, government, and parents. Cases of narcotics abuse among high school youth have entered a critical stage, for this reason it is necessary to take preventive measures in the form of education. The purpose of this community service is to increase and develop youth knowledge about the dangers of drug abuse for health. The planned outcome is to increase the knowledge, understanding and awareness of adolescents about the dangers of drug abuse for adolescents.